Public policies for the strengthening of family farming in the Global South - Michael MacLennan; Thomas Patriota; Francesco Maria Pierri (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
This special edition of Policy in Focus aims to follow up on discussions and debates instigated by the International Year of Family Farming (IYFF 2014) by drawing attention to specific cases as well as more general policy recommendations related to family farming in countries of the Global South. It is the product of a collaboration between the International Policy Centre for Inclusive Growth of the United Nations Development Programme (UNDP IPC-IG), the Food and Agriculture Organization of the United Nations (FAO) and the Ministry of Agrarian Development (MDA) of Brazil. [...]
Keywords: 330; public policies; strengthening; family farming; global south